The relationship between self-concept and achievement in the Inventory of Developmental Tasks - Arrington, George Edwin 1937-
The relationship between self-concept of kindergarten children and their achievement in the Inventory of Developmental Tasks was determined in this study. The implications of the findings for purposes of curricular innovations in the programs for kindergarten were then derived.